IMPROVING THE EFFICIENCY OF THE PRODUCTION PROCESS IN THE SURFACE MOUNT TECHNOLOGY (SMT) INDUSTRY WITH A LEAN MANUFACTURING APPROACH - Zuryensi Zuryensi; Muhammad Asrol (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2022)
The Manufacturing industry needs commitment for continuous improvements in various aspects of technology and business processes currently in-use. This allow companies to streamline processes and costs incurred in production operations, so that productivity continues to increase and they are no waste elements occurs. This study aims to analyse the non-value added/wasted Sufrace Mount Technology (SMT) production process and based on results formulate recommendations to mimimize these negative factors to increase Surface Mount Technology (SMT) production efficiency. Additionally this study allows to conduct sensitivity analysis and introduce cost benefit factors in optimised production process. Method uses in this researches is VSM, VALSAT, WAM, RCA, and FMEA. Based on the results of Current State VSM, the PCE value is 9.18%, which means that the production process is not efficient. Using VALSAT method with PAM tools allow us to calcute following values: VA is 84.5, NVA is 420 and NNVA is 60. Utilizing WAM we can identify that waste in aspects like waiting, transportation and motion have the highest engagment in current non-optimized process. This is also exposed to RCA, root cause of current inefficencies in SMT production process are caused by capacity of the chip mounting and not properly utilisation of IC mounting machines. It is proven that the highest RPN on FMEA is motivated by engine capacity that is not used efficently. Authors suggest to create a new line in the SMT process by using same number of Chip and IC mounting machines with addition of several new machines to support current process.